Menelaah Hubungan antara Kompensasi dan Retensi Karyawan : Tinjauan Literatur dan Arah Masa Depan - Indrawan Syah; M. David Amirulloh; Agus Jamal; Nafia Ilhama Qurratu’aini (Universitas 45 Surabaya, 2025)
Employees are the most vital assets in the success of a company's operations. In efforts to maintain employee retention, compensation plays a crucial role in influencing employee motivation and performance. Compensation, which includes bonuses, allowances, a conducive work environment, and roles that support skill development, significantly enhances employee productivity and performance. This study aims to examine the relationship between compensation and employee retention through a systematic literature review. By employing the Systematic Literature Review method, this research identifies how effective forms of compensation can impact employee retention and offers future directions for further research. The findings indicate a positive correlation between compensation and employee performance, where increased compensation can boost employee motivation and loyalty to the company.